2009
DOI: 10.2519/jospt.2009.3040
|View full text |Cite
|
Sign up to set email alerts
|

Foot Kinematics During a Bilateral Heel Rise Test in Participants With Stage II Posterior Tibial Tendon Dysfunction

Abstract: abnormal kinematics during a heel rise task. 41 The normal combined action of the posterior tibialis and triceps surae muscles is thought to produce ankle plantar flexion with inversion during a heel rise task. 15,23,33 Clinically, an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 44 publications
3
44
1
Order By: Relevance
“…Following a 10-week strengthening program, the PTTD group exhibited a 58% increase in strength, concomitant with significant reductions in pain. Houck et al 8 also reported that patients with PTTD exhibited 30% reduced ankle invertor strength compared to age-matched controls. However, while these 2 studies indicate that ankle invertor strength may be associated with PTTD, the individuals with PTTD in the aforementioned studies were at stages II to IV of the condition, and no study has investigated individuals with stage I PTTD for potential differences in ankle invertor strength.…”
Section: Biomechanical and Clinical Factors Related To Stage I Posteriormentioning
confidence: 95%
See 1 more Smart Citation
“…Following a 10-week strengthening program, the PTTD group exhibited a 58% increase in strength, concomitant with significant reductions in pain. Houck et al 8 also reported that patients with PTTD exhibited 30% reduced ankle invertor strength compared to age-matched controls. However, while these 2 studies indicate that ankle invertor strength may be associated with PTTD, the individuals with PTTD in the aforementioned studies were at stages II to IV of the condition, and no study has investigated individuals with stage I PTTD for potential differences in ankle invertor strength.…”
Section: Biomechanical and Clinical Factors Related To Stage I Posteriormentioning
confidence: 95%
“…However, these authors did not measure AHI, so comparisons are difficult. Both Neville et al 24 and Houck et al [8][9][10] measured AHI in individuals with stage II PTTD and found significantly lower values than in healthy controls. Therefore, the results of the current study suggest that arch structure, while perhaps not a contributing factor in stage I PTTD, may be more apparent in later stages of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…To date, foot and ankle kinematics in persons with stage 2 AAFD have only been evaluated during the bilateral heel-rise test. 11 A previous study by Houck and colleagues 11 found that individuals with unilateral AAFD achieved similar bilateral heel-rise height, as well as similar forefoot (first metatarsal relative to calcaneus) and rearfoot (calcaneus relative to tibia) PF excursions, to that of healthy controls. However, the heel-rise height in persons with AAFD was achieved with the forefoot in significant pronation.…”
Section: T T Conclusionmentioning
confidence: 99%
“…2 Prolonged pronation likely overloads the posterior tibialis tendon, resulting in localized degenerative changes, impaired muscle strength capacity, and pain. In the presence of flatfoot deformity, the result is typically increased hindfoot eversion, 16,17 increased transverse plane foot motion, 28,29,38 inefficient propulsion during locomotion, 32 and diminished plantar flexion moment. 28,32 The actions of the hip extensors and abductors are essential during walking.…”
Section: Women With Posterior Tibial Tendon Dysfunction Have Diminishmentioning
confidence: 99%
“…The single-leg heel raise task is considered a clinical test of plantar flexor strength 22,27 and posterior tibialis muscle function. 17 Bilateral hip extensor and hip abductor isometric strength and endurance were assessed using the PrimusRS dynamometer (BTE Technologies, Hanover, MD). In healthy participants, the testretest reliability assessed by ICC for hip strength was 0.87 (extension) and 0.80 (abduction), and for hip endurance was 0.88 (extension) and 0.27 (abduction).…”
Section: Instrumentation Questionnaires and Functional Testsmentioning
confidence: 99%